SISTEM PENDUKUNG KEPUTUSAN PENILAIAN DABAT PUBLIK SESI I CALON WALIKOTA TERNATE 2020 MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY (MAUT) - Ilham Djufri (JNSTA ADPERTISI JOURNAL, 2021)
Decision support systems provide interrelational tools that enable decision making to carry out various analyzes using available methods. The purpose of this study is to provide literacy and enlightenment to the people of Ternate City that to assess something related to academic criteria must use methods. In the calculation analysis, the data used is the debate assessment data for the one-session Mayor / Deputy Mayor of Ternate City which was held on 27 October 2020, with data collection techniques for distributing questionnaires and interviews. The sample objects of the questionnaire taken were Lecturers, Teachers, Civil Servants and Journalists, using 4 (four) Criteria; Thinking Logic, Thinking Systematic, Synthesis Analysis Ability, and Discourse Analysis Kemempuan, and 4 (four) alternatives, namely the candidate pairs MAJU-A1, TULUS-A2, MHB-GAS-3 and YAMIN-ADA_A4. The data analysis algorithm method used is the Multi Attribute Utility Theory (MAUT) with the result of YAMIN-ADA_A4 as the first ranking with a value of 0.65.